Pengaruh penambahan tepung daun kelor (Moringa oleifera) terhadap kandungan zat besi dan daya terima boba (tapioca pearl) - Anggraeni Oktavia Rohmadhani; Dwi Sarbini (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Iron deficiency anemia remains a major nutritional problem among adolescents, with a prevalence of 15.5% in Indonesia and 57.7% in Central Java. Boba (tapioca pearls), a beverage popular among adolescents, generally contains low levels of iron. Moringa leaves (Moringa oleifera) are known to be rich in iron, approximately 28 mg per 100 g in powder form, and thus have potential as a natural fortificant in boba products. This study aimed to analyze the effect of Moringa leaf powder addition on the iron content and acceptability of boba. This study employed an experimental design using a Completely Randomized Design (CRD) with one factor, consisting of four treatments: 0%, 5%, 10%, and 15% Moringa leaf powder addition, each with three replications. Iron content was analyzed using Atomic Absorption Spectrophotometry (AAS), while acceptability was evaluated by 35 semi-trained panelists using a 7-point hedonic scale. Data were analyzed using One Way ANOVA followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that the addition of Moringa leaf powder significantly affected both the iron content and acceptability of boba (p<0.05). The iron content increased with higher concentrations of Moringa leaf powder, ranging from 0.059 µg/100 g to 3.637 µg/100 g. The highest acceptability was observed in the 5% treatment, categorized as “liked,” while the 15% treatment showed the lowest acceptance. In conclusion, the addition of 5% Moringa leaf powder is the optimal formulation, as it enhances iron content while maintaining consumer acceptability.